STRATEGI GURU SD DALAM MENGHADAPI SISWA YANG MENGALAMI KETERLAMBATAN MEMBACA - Bulandari, Siti; Haifaturrahmah, Haifaturrahmah; Fujiaturrahman, Sukron (Jurnal Ilmiah Telaah, 2026)
This study aims to analyze elementary school teachers' strategies in dealing with students who experience reading delays through a Systematic Literature Review (SLR) approach to scientific publications from 2015 to 2025. Data were collected from various reputable sources such as Scopus, DOAJ, and Google Scholar, then analyzed based on the focus, variables, and effectiveness of the intervention strategies used. Reading ability is the main foundation for literacy mastery and student academic achievement, but many students still have difficulty recognizing letters, combining syllables, and understanding the meaning of what they read. The results of the review show three main focuses of teacher strategies, namely the application of differentiated, phonics, and multisensory learning; the use of technology and innovative learning media; and collaboration between teachers, parents, and schools. Phonics and multisensory strategies have been proven effective in improving decoding skills, fluency, and reading comprehension. Meanwhile, digital learning technology and cooperation between schools and families also contribute to the success of literacy interventions. However, limitations in teacher training, access to technology, and parental participation remain major challenges. This study emphasizes the importance of improving teacher competence, optimizing technology, and cross-party collaboration to strengthen students' basic literacy in a sustainable manner.